KONTRIBUSI KKG GURU CENDEKIAWAN DALAM PENINGKATAN KOMPETENSI PROFESIONAL GURU SEKOLAH DASAR DI KECAMATAN MANIANGPAJO KABUPATEN WAJO - Yuli Ardanawati; Burhanuddin; Nurcaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the contribution of the Teachers Working Group (KKG) of the Cendekiawan Cluster in improving teachers’ professional competence in Maniangpajo District, Wajo Regency, and to identify the supporting and inhibiting factors in its implementation. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The research subjects consisted of the head, secretary, members of the KKG, and the cluster supervisor. The results show that the KKG contributes through program planning, instructional discussions, preparation of teaching materials, and learning evaluation activities that enhance teachers’ mastery of subject matter and teaching skills. Supporting factors include structured work programs and supervision support, while inhibiting factors include low attendance and limited participation of some members.